A Cross-level Interaction Effects of Organizational Climate on the Relationship between Personal Factors and Art Teachers’ Professional Leadership in Higher Educational Institutions in Hunan Province: A Multilevel Analysis - Ye, Chen; Moonmuang , Sukhum; Senarith, Prapatpong (Journal of Roi Kaensarn Academi, 2023)
The objectives of this research were: (1) To study the organizational contextual effects that affect Art teachers’ professional leadership, (2) to study the effects of personal factors on Art teachers’ professional leadership when the influence of organizational climate remains unchanged, (3) to study the effects of organizational climate on Art teachers’ professional leadership in the organizational level when controlling the organizational contextual effects constant, and (4) to study the cross-level interaction effect of organizational climate on the relationship between personal factors and Art teachers’ professional leadership. The research method was a quantitative survey research, Multilevel Structural Equation Model (MSEM), including individual and organizational levels. Population were divided into 2 sub-populations that were hierarchically nested namely (1) Art teachers and (2) administrators of Fine Art faculty who were working in public colleges and universities in Hunan Province, people’s republic of China in the academic year 2023. The sample of the Art teacher group and administrator group were selected by the multi-stage proportional random sampling method, the total sample were 300 art teachers at the individual level and 100 administrators at the organizational level. The research findings revealed that (1) The art teachers’ professional leadership was affected by the organizational contextual effects; (2) When the influence of organizational climate remains unchanged, the teaching-age and characteristics in the personal factors had a direct impact on art teachers’ professional leadership while gender, self-efficacy and personal leadership skill did not significantly affect art teacher leadership; (3) without considering the organizational climate of a certain university, the organizational climate had an effect on art teachers’ professional leadership; (4) organizational climate had cross-level interaction with individual characteristics and personal leader skill effects on art teachers’ professional leadership, but the cross-interaction with gender, Teaching-Age, and self-efficacy found not significantly effect on Art teachers’ leadership.